2018
DOI: 10.18203/2349-3933.ijam20180999
|View full text |Cite
|
Sign up to set email alerts
|

A study in prevalence of diabetic nephropathy in recently detected cases of type 2 diabetes mellitus as evidenced by altered creatinine clearance, urinary albumin and serum creatinine, with special emphasis on hypertension, hypercholesterolemia and obesity

Abstract: Original Research ArticleA study in prevalence of diabetic nephropathy in recently detected cases of type 2 diabetes mellitus as evidenced by altered creatinine clearance, urinary albumin and serum creatinine, with special emphasis on hypertension, hypercholesterolemia and obesity Vitan Patel, Minal Shastri*, Nisha Gaur, Prutha Jinwala, Abhishek Y. Kadam INTRODUCTIONDiabetes Mellitus (DM) is one of the commonest diseases in the world, especially the industrialized world. But recently, the "Silent epidemic" of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
2
9
1
Order By: Relevance
“…In addition, less than the results mentioned by Patel V et al, in their study, where total of 43 patients out of 100 patients were detected to have Diabetic Nephropathy [10] .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In addition, less than the results mentioned by Patel V et al, in their study, where total of 43 patients out of 100 patients were detected to have Diabetic Nephropathy [10] .…”
Section: Discussioncontrasting
confidence: 55%
“…Complications of diabetes contribute greatly to the increased mortality and morbidity associated with this disease. Diabetic complications are customarily divided into two main categories: Macrovascular complications, including heart disease and stroke, and microvascular complications, which include retinopathy, nephropathy, and neuropathy, 2077 Diabetic nephropathy and microalbuminuria are also strong predictors of cardiovascular and overall morbidity and mortality in patients of diabetes, and hence vital indicators in the patients [10] .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The prevalence among Indian type 2 diabetics is 5-9% 10,11 and may even be higher according to recent studies. 12 Prevalence (p) was hence taken as 9%, q as 93%, and L as 5% (for 95% confidence interval). Sample size was calculated to be approximately 130.…”
Section: Methodsmentioning
confidence: 99%
“…So, not only this study is important due to the enormity of human population that has been affected with diabetes but also this study takes priority primarily due to the fact that it aims to evaluate HbA1c and its correlation with lipid profile among Indian prediabetics as India is the diabetic capital of the world [22] and the study population is chosen from Karnataka State as this state has reported 3 rd highest death rate due to Diabetes in the year 2017 among all the states of India [23,24]. Our study aims to evaluate the lipid profile pattern and demographic data of prediabetics in Bangalore and to identify correlations between their HbA1c levels and lipid profile along with demographic data.…”
Section: Introductionmentioning
confidence: 99%